The effect of temperature to the performance of coupled bent optical waveguides - Uenverdi, N. Oezlem; Uenverdi, N. Aydan; Canbay, Cahit (IEEE, 2007)
Optical fibers which are the basic elements of the optical communication technology, that progressed rapidly during the recent years, have become the key element in many industrial applications. In this study, coupled optical waveguides which are in use in many areas such as directional couplers, sensors, multiplexers, amplifiers and filters, were analyzed. The impact of temperature on the performance of circularly bent, bare, weakly guiding, lossless, multimode and slab optical waveguides was investigated The coupling between pair TE modes was observed to be higher than the coupling between other modes. Coupled optical waveguides were analyzed in an ambient temperature of 100C. The change in the modal propagation constant was observed to decrease as the ambient temperature increases.
Keywords: BENDING LOSSES; MULTIMODE; FIBERS; Computer Science; Engineering; Telecommunications